PENGARUH PERPUTARAN PIUTANG DAN HUTANG TERHADAP ARUS KAS OPERASI. STUDI PADA PT EXER INDONESIA - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2015)
This study is analyzed the impact of Account Receivables and Account Payables Turnover to Operating Cash Flow in PT Exer Indonesia. Data is collected from PT Exer Indonesia from 2009 to 2013 and analyzed quantitatively by SPSS which are Partialy and Simultaneously Regression Test. The result of this study showed that Account Receivables Turnover partialy had influence to Operating Cash Flow, Account Payables Turnover partialy had not influence to Operating Cash Flow, but Account Receivables and Account Payables Turnover simultaneously has influence to Operating Cash Flow of PT Exer Indonesia.